Constitutional and legal foundations of the unified system of public power in the Russian Federation (regional aspect) - O. A. Kozhevnikov; A. V. Chuklin (Правоприменение)
Within the framework of this study, theoretical approaches to understanding public power in the context of various areas of scientific knowledge are analyzed. In the course of this work, attention is drawn to the constitutional approach, according to which the unified system of public power in the Russian Federation includes two independent, but interacting levels: state and municipal. In this regard, it is noted that the federal legislation adopted in the development of constitutional provisions significantly expands this approach and actually establishes a three-level system of public power. As a consequence, the problem of substantiating the existence of a unified system of public power in the subjects of the Russian Federation is being actualized. Using the system-logical method of research, the provisions of Federal Law No. 414-FZ of December 21, 2021 "On the general principles of the organization of public power in the Subjects of the Russian Federation", which normatively establish the category of a unified system of public power in the subject of the Russian Federation, are analyzed in the work. Certain provisions of the said federal law are not fully consistent with each other and with other federal legislation, including with regard to the constitutional and legal understanding of the unified system of public power. At the same time, attention is drawn to the fact that the territorial principle cannot underlie the allocation of an independent regional level of public power, since the derivation of public power from the understanding of "state" and "statehood", on the basis of equality of the subjects of the Russian Federation as a constitutional principle, makes it impossible to have a different ratio of intra-system connections in the systems of public power in the subjects of the Russian Federation. The formal legal approach made it possible to trace the dynamics of changes in the constitutional (statutory) legislation of the subjects of the Russian Federation, depending on the understanding of the place of state authorities of the subjects of the Russian Federation in the unified system of public power. Various normative variations of the constitutional (statutory) legislation of the subjects of the Russian Federation, aimed at bringing it into line with the same constitutional text, indicates the absence of an unambiguous and uniform understanding of the place of the system of state authorities of the subjects of the Russian Federation in the unified system of public power in the country. Thus, it is noted that the development of a uniform approach based on the positions of the Constitutional Court of the Russian Federation, which are mandatory for all subjects of legislative activity, to the content of the category "unified system of public power in the Russian Federation" is fully capable of ensuring the goal of its formation stated in Part 3 of Article 132 of the Constitution of the Russian Federation in compliance with all constitutional principles and norms. In this regard, within the framework of the unified system of public power in Russia, we should not talk about independent unified systems of public power in the subjects of the Russian Federation, but should focus on the formation of a unified system of public power throughout the territory of our state.